2016
DOI: 10.1155/2016/8312158
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Maternal Anxiety as a Risk Factor for Preterm Birth and the Effects of Heterogeneity on This Relationship: A Systematic Review and Meta-Analysis

Abstract: Background. Systematic reviews (SR) and meta-analyses (MA) that previously explored the relationship between prenatal maternal anxiety (PMA) and preterm birth (PTB) have not been comprehensive in study inclusion, failing to account for effects of heterogeneity and disagree in their conclusions. Objectives. This SRMA provides a summary of the published evidence of the relationship between PMA and PTB while examining methodological and statistical sources of heterogeneity. Methods. Published studies from MEDLINE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
58
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(63 citation statements)
references
References 65 publications
(66 reference statements)
1
58
1
3
Order By: Relevance
“…Studies have shown that negative maternal emotions during pregnancy are associated with an adverse pregnancy outcome. The effect of high antenatal anxiety on both low birth weight for gestational age and preterm delivery are the most reported results [1,3,9,19]. On the contrary, no significant correlation between antenatal maternal anxiety and gestational age at birth was reported [20].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that negative maternal emotions during pregnancy are associated with an adverse pregnancy outcome. The effect of high antenatal anxiety on both low birth weight for gestational age and preterm delivery are the most reported results [1,3,9,19]. On the contrary, no significant correlation between antenatal maternal anxiety and gestational age at birth was reported [20].…”
Section: Discussionmentioning
confidence: 99%
“…40 Systematic reviews including meta-analyses have demonstrated an association between anxiety and preterm birth. [43][44][45] A substantial reduction in heterogeneity between the studies was noted when analyses were restricted to state anxiety and pregnancy-specific anxiety, with odds ratios similar for both (OR, 1.70; 95% CI, 1.33-2.18; OR, 1.67; 95% CI, 1.35-2.07, respectively). 43 Antenatal depression is also thought to be associated with preterm birth, though the effect size is typically smaller, and fewer studies demonstrate statistically significant associations.…”
Section: The Mind: Psychosocial Risk Factorsmentioning
confidence: 97%
“…[43][44][45] A substantial reduction in heterogeneity between the studies was noted when analyses were restricted to state anxiety and pregnancy-specific anxiety, with odds ratios similar for both (OR, 1.70; 95% CI, 1.33-2.18; OR, 1.67; 95% CI, 1.35-2.07, respectively). 43 Antenatal depression is also thought to be associated with preterm birth, though the effect size is typically smaller, and fewer studies demonstrate statistically significant associations. 40 Although a meta-analysis reported an association between antenatal depression and preterm birth (RR, 1.39; 95% CI, 1.17-1.61), Grote et al noted significant heterogeneity (I 2 , 61%; P Ͻ .001) and publication bias suggesting the association may not in fact be present.…”
Section: The Mind: Psychosocial Risk Factorsmentioning
confidence: 97%
See 1 more Smart Citation
“…Anxiety and depression during pregnancy often coexist (O'Hara, Wisner, & Asher, 2014;Schmeid et al, 2013) and are associated with postnatal depression (Koutra et al, 2014;Obgo et al, 2018). Antenatal stress, anxiety and depression represent key risk factors in the aetiology of preterm birth (Eastwood, Obgo, Hendry, Noble, & Page, 2017;Rose, Pana, & Premji, 2016;Staneva, Bogossian, Pritchard, & Wittkowski, 2015). An association has also been identified between antenatal stress, anxiety and depression and low birthweight infants (Khashan et al, 2014;Saeed, Rashid, Ahmed, Naqvi, & Tabassum, 2016).…”
Section: Introductionmentioning
confidence: 99%